2022
DOI: 10.1093/eurjpc/zwac184
|View full text |Cite
|
Sign up to set email alerts
|

Coronary microvascular dysfunction is an independent predictor of developing cancer in patients with non-obstructive coronary artery disease

Abstract: Background Cardiovascular disease and cancer share common pathogenesis and risk factors. Coronary microvascular dysfunction (CMD), reflecting impaired coronary microvascular dilation in response to stress, is related to a higher risk of major cardiovascular events; however, its association with cancer has not been explored. Methods A retrospective study on 1042 patients with non-obstructive coronary artery diseases was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Therefore, the pharmacological management of ICI-derived early coronary endothelial dysregulation might serve as a druggable target for the mitigation of both cardiac dysfunction and vascular-driven CVAEs by anti-PD-1 therapy. Importantly, microvascular endothelial dysfunction is an independent predictor of cancer development and progression, as it is shown that patients with nonobstructive coronary artery diseases have a higher incidence of malignancies [34,65]. Targeting microvascular coronary endothelial dysfunction in anti-PD-1 therapy might facilitate the parallel treatment of both cancer progression and CVAEs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the pharmacological management of ICI-derived early coronary endothelial dysregulation might serve as a druggable target for the mitigation of both cardiac dysfunction and vascular-driven CVAEs by anti-PD-1 therapy. Importantly, microvascular endothelial dysfunction is an independent predictor of cancer development and progression, as it is shown that patients with nonobstructive coronary artery diseases have a higher incidence of malignancies [34,65]. Targeting microvascular coronary endothelial dysfunction in anti-PD-1 therapy might facilitate the parallel treatment of both cancer progression and CVAEs.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, more attention has been paid to the hazards of CMD. Rajai et al reported that CMD was closely related to the development of cancer in patients with non-obstructive coronary artery disease [ 28 ]. The cerebral-coronary connection study suggested that CMD patients were more likely to have cognitive impairment [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, an increasing number of epidemiological and clinical studies have reported that patients with cardiovascular diseases are at higher risk of developing cancer [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. A very recent meta-analysis revealed an increased risk of incident cancer after a CAD event, particularly for lung and colorectal cancers, suggesting that detailed cancer surveillance programs should be implemented in patients with CAD to reduce cancer-related morbidity and mortality [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, subjects who have developed myocardial infarction (MI) have higher short- and long-term hazard ratios for cancer than those without MI [ 4 ], and patients with atherosclerotic cardiovascular diseases exhibit two-fold higher incidence of cancer development than those with non-atherosclerotic CVD [ 6 ]. Moreover, coronary microvascular dysfunction is associated with cancer incidence in patients presenting with non-obstructive coronary artery disease [ 7 ]. CAD seems to be associated particularly with colorectal and lung cancers [ 1 ].…”
Section: Introductionmentioning
confidence: 99%